Translocation as a Population Restoration Technique for Northern Bobwhites: A Review and Synthesis - James A. Martin; Roger D. Applegate; Thomas V. Dailey; Michelle Downey; Beth Emmerich; Fidel Hernández; Mark M. McConnell; Kelly S. Reyna; Dale Rollins; Rebekah E. Ruzicka; Theron M. Terhune II (National Quail Symposium Proceedings, 2017)
Northern bobwhite (Colinus virginianus) abundance has declined precipitously for decades across much of the species range, to the point of widespread local, regional, and statewide extirpation. Because of successful translocations of other gallinaceous birds, bobwhite enthusiasts increasingly call for use of the approach. Consequently, the National Bobwhite Technical Committee (NBTC), on behalf of state agencies, requested a review and recommendation by the NBTC Science Subcommittee. Thus, our paper is co-authored by invited experts and includes reviews of peer-reviewed publications, manuscripts in these proceedings, state agency reports, experience by co-authors, and a survey of perspectives on translocations by state wildlife agency members of the NBTC. We discuss the state of science on key aspects of bobwhite conservation, offer best management practices (BMPs) for using translocation as a potential bobwhite restoration technique, and suggest ways to reduce uncertainty about implementation. We note that although conservationists operate on a relatively solid foundation of improving bobwhite abundance via increased quantity, connectivity, and quality of habitat, population restoration success to- date is relatively rare and unpredictable. Similarly, some past translocations have been unreliable with an abundance of failures and inadequate experimental designs. We conclude that because of major uncertainties regarding habitat, population phenomena (e.g., Allee effect) and restoration techniques, outcomes of translocations remain unpredictable; thus, future efforts must be a part of sound and rigorous peer-reviewed research. To improve scientific efforts, we recommend the following BMPs for future translocations: (1) target bobwhite abundance should be >800 post-translocation which will likely necessitate ≥600 ha of suitable and accessible habitat while a larger (e.g., >800 ha) area will be needed in areas with lower carrying capacity and when sites are highly fragmented or isolated, (2) personnel should identify and avoid stressors to bobwhites in all phases of the translocation process (i.e., capture, holding, transportation, and release), (3) source populations should be disease free and from similar environments and latitude; preferably from the nearest suitable source, (4) conspecifics should be present on recipient sites (5) birds should be released just before the breeding season (i.e., March or April), and (6) the translocation should incorporate robust short- and long-term bird (i.e., abundance and/or density) and habitat monitoring efforts (i.e., the Coordinated Implementation Program (CIP) of the National Bobwhite Conservation Initiative (NBCI)). In conclusion, we note that translocation of bobwhites is not a panacea for broad scale restoration of bobwhites; however, the technique should remain at the forefront of bobwhite science, taking into account knowledge of the species’ life history and ecology, so that a practical and reliable solution can be developed. We recognize this paper is just the beginning of vigorous debate, testing of concepts, and on-the ground implementation of successful bobwhite conservation.
Keywords: northern bobwhite; allee effect; colinus virginianus; population restoration; restocking; translocation